FRI0289 Cerebrovascular disease in the antiphospholipid syndrome. (15th June 2017) - Estévez, M; Argibay, A; Rodriguez, L; Freire, M; Gimena, B; Fernández-Martín, J; Rivera, A
Abstract : Background: Antiphospholipid syndrome (APS) is a thrombophilic disorder characterized by recurrent arterial and venous thrombosis, and also pregnancy losses associated to antiphospholipid antibodies (APA). Cerebrovascular disease (CVD) is the most common and severe arterial thrombotic manifestation in patients with APS. Objectives: 1.To determine the prevalence and the type of CVD in patients with APS. 2.To compare the recurrent strokes, affected brain areas, hospitalization, treatment and mortality between patients with CVD, with and without APS. Methods: Retrospective and, descriptive study of patients with APS (Sidney criteria) and CVD followed for a long period of time in a specific Systemic Autoimmune Diseases and Thrombosis Unit. Subsequently, retrospective case-control study was performed. Case definition: patients with CVD attributable to APS. Control definition: patients with CVD without APS. The controls were matched with cases by sex and age (within the same decade). Chi-square and t-student were used, using the statistical package SPSS22.0. Results: 25 patients (25/88 28, 4%) had CVD, 19 (76%) of primary APS and 6 (21%) of secondary APS. 17 patients (71, 6%) were female. The mean age was 57, 48±21, 52 [range 13–89], with a mean follow-up of 8, 64±6, 72 years. 24% of patients had atrial fibrillation, 80% had one cardiovascular risk factor and 48% had two or more factors (hypertension 68%, hypercholesterolemia 36%, diabetes 20%, tabaquism 4%). Echocardiographic study was performed in 72% of patients with APS. Mitral valve was mainly involved. Most CVD were ischemic events (92%). The brain areas most involved were the basal ganglia (36%), together with the parietal and temporal lobe (16% respectively). 40% had two or more affected regions. 44% of the patients had two or more episodes of stroke. Lupus anticoagulant was positive in 40%, anticardiolipin antibodies in 76% and anti-β2 glycoproteinI antibodies in 20%.No differences were found with isotypes of APA and recurrent thrombosis or mortality. The treatment applied was oral anticoagulants (OAC) (48%), antiplatelet therapy (APT) (20%) and low molecular weight heparin (20%). In 10 patients (40%) CVD was diagnosed before APS (mean 8.64±6.7 years). The mortality was 44% and 40% of the patients were hospitalized more than once. When we compared the groups: treatment, performed echocardiogram, valvular disease, affected brain areas, recurrent strokes and follow-up time, revealed significant differences (see table 1 ).OAC were more used in the patients with APS and APT was the most common in control group. Valvular disease was more frequent in case group. The brainstem and the frontal lobe were the areas more affected in patients without APS.The number of strokes was higher in APS group. The patients with CVD and APS had a long-term follow-up. Conclusions: The prevalence of CVD in our series of APS was 28.4% and most often were ischemic events. Most of the patients were women with high recurrent strokes and mortality. No differences were found with isotypes of APA and recurrent thrombosis or prognosis. CVD with APS patients had more recurrent strokes and longer follow-up. Disclosure of Interest: None declared